ETHNOBOTANY STUDY OF CEMPELAHU (Cordia dichotoma G. Forst) IN TAMIANG HILL FOREST OF TANAH LAUT REGENCY AS A POPULAR SCIENTIFIC BOOK - Wahyu Dita Zulkafifah; Dharmono Dharmono; Muhammad Zaini (ATRIUM PENDIDIKAN BIOLOGI, 2021)
Cempelahu plant (Cordia dichotoma. G. Forst) has distribution and benefits in the Bukit Tamiang-forest area. This study aims to describe the ethnobotany of cempelahu plant in the Bukit Tamiang-forest area, Tanah Laut Regency, to describe the validity and practicality of the contents of the popular scientific book Cordia dichotoma. G. Forst. The research method used is descriptive quantitative research followed by formative evaluation of the Tessmer test for the feasibility of BIP which was developed through the stages of Self evaluations, Expert review and one to one test. The results showed that Cordia dichotoma G. Forst plant has a tap root habit, simpodial stems are round, alternate ovate leaves, compound flowers are bordered, and the fruit is compound type of buni fruit. This plant is used as a medicine for ulcers and can disguise scars. Cordia dichotoma plant. G. Forst has the regional name "cempelahu" taken from the Banjar Campah language which means itching. The results of the development of teaching materials in the form of Popular Scientific Books on the expert review by 2 validators have very valid validation results and the results of the practicality of the contents on the individual test (one to one) by 3 students have very good results.